Photoanode/Electrolyte Interface Stability in Aqueous Dye‐Sensitized Solar Cells. Issue 2 (27th July 2016) - Galliano, Simone; Bella, Federico; Gerbaldi, Claudio; Falco, Marisa; Viscardi, Guido; Grätzel, Michael; Barolo, Claudia
Abstract: O'Regan and Grätzel conceived a dye‐sensitized solar cell (DSSC), which operates as an artificial photosynthetic system converting solar light into electricity. Nevertheless, it is only recently that the scientific community is focusing on truly aqueous DSSCs that use water as electrolyte, thus avoiding any flammable and toxic organic solvents. The most critical aspect of these devices is the photoanode/electrolyte interface. Indeed, it is necessary to select dyes that chemisorb onto the semiconductor layer while allowing the aqueous electrolyte to thoroughly impregnate the mesostructure of the electrode; at the same time, it is necessary to avoid the anchoring unit of the dye to be hydrolyzed by water, thus causing the detachment of the sensitizer from the active material particles. This requires a thorough analysis of the structure–property relationships, in particular the evaluation of the chemical formula, stability, and performances of the dyes on the electrode surface in truly aqueous environment. Herein, we investigate nine different sensitizers, selected based on their different properties in terms of light absorption, chemical structure, and hydrophobic/hydrophilic nature. Wettability, resistance to dye desorption, and spectral variations of sensitized photoanodes, along with the photovoltaic performance of the resulting devices, are systematically investigated to identify some useful guidelines to choose and design suitable dyes of different colors for truly aqueous DSSCs. Abstract : Solar cells work with water ! When moving towards aqueous solar cells, the best conditions occur when photoanode wetting is achieved and dye desorption is avoided. This work provides suggestions on how to identify the relationship between the molecular structure of dyes and the stability in water of the sensitizers and also some useful guidelines to select and design suitable dyes for 100 % aqueous dye‐sensitized solar cells.